2023
DOI: 10.1002/cdt3.55
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological practice in the differential diagnosis of mucoepidermoid carcinoma from neoplasms with mucinous component

Abstract: Background: The differential diagnosis of mucoepidermoid carcinoma (MEC) from neoplasm undergoing mucinous features brings more pitfalls to pathologists. Combining specific MAML2 gene rearrangement and histological characteristics may be the solution. Methods: Twenty-five tumors with mucinous components were selected for differential diagnosis of MEC. All the cases were detected for MAML2 gene rearrangement. The cases diagnosed as MEC were classified into four variants: classic, oncocytic, Warthin-like, and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…These tumors are often high-grade and invasive. 4 In the literature we have accessed in the last 20 years, we have compiled Table 1 summarizing case reports that raise suspicion of malignant salivary gland tumors due to widespread metaplastic changes in the PA. 1,[6][7][8][9][10][11][12][13][14] In this case, a prior FNAB performed elsewhere prompted the excision of the lesion. While evaluating fine needle aspiration biopsies of pleomorphic adenomas can be challenging due to their diverse metaplastic components, the Milan reporting system may place such aspirates in risk categories (III, IVA, IVB, V, or even VI).…”
Section: Discussionmentioning
confidence: 94%
“…These tumors are often high-grade and invasive. 4 In the literature we have accessed in the last 20 years, we have compiled Table 1 summarizing case reports that raise suspicion of malignant salivary gland tumors due to widespread metaplastic changes in the PA. 1,[6][7][8][9][10][11][12][13][14] In this case, a prior FNAB performed elsewhere prompted the excision of the lesion. While evaluating fine needle aspiration biopsies of pleomorphic adenomas can be challenging due to their diverse metaplastic components, the Milan reporting system may place such aspirates in risk categories (III, IVA, IVB, V, or even VI).…”
Section: Discussionmentioning
confidence: 94%
“…14 For example, MEC devoid of mucocytes can be challenging to differentiate from mammary analog secretory carcinoma with squamoid cell mimickers, 18 and oncocytic MEC with limited amount of both mucus-secreting cells and squamoid cells can be difficult when distinguishing from oncocytic carcinoma, acinar cell carcinoma, and adenocarcinoma, not otherwise specified. 19 Therefore, acknowledging the diverse morphologic patterns of MEC is important for pathologists to make a proper diagnosis which requires further molecular testing. In particular, similar to the p63 negativity of our cases, Bishop et al 15 recently reported 10 MAML2 fusion-confirmed MEC cases that are devoid of squamous cells both histologically and immunohistochemically and also emphasized the need for updated definition of the MEC.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, however, even with the routinely available ancillary tests, pathologists frequently encounter troublesome cases in which immunostaining is not useful 14 . For example, MEC devoid of mucocytes can be challenging to differentiate from mammary analog secretory carcinoma with squamoid cell mimickers, 18 and oncocytic MEC with limited amount of both mucus-secreting cells and squamoid cells can be difficult when distinguishing from oncocytic carcinoma, acinar cell carcinoma, and adenocarcinoma, not otherwise specified 19 . Therefore, acknowledging the diverse morphologic patterns of MEC is important for pathologists to make a proper diagnosis which requires further molecular testing.…”
Section: Discussionmentioning
confidence: 99%